Մխիթարյանների գործունեությունը հայ հասարակական մտքի գնահատմամբ - Թաթուլ Ասոյան (ՀՀ ԳԱԱ հրատ.)
Деятельность Мхитаристов всегда находилась в центре внимания армянской обществнной мысли. Высказывались разные мнения, и даже такие авторитетные мыслители, как М. Налбандян и Лео, не дали ей однозначной оценки. Из выдвинутых вопросов можно выделить вопросы религиозной принадлежности Мхитаристов, отношение к грабару и ашхарабару. Исследования показывают, что Мхитаристы сыграли особо важную роль в арменоведении и внесли неоценимый вклад именно в эту сферу. The activities of the Mkhitarists has always been in the centre of Armenian public thought. Even such authorized writers, as M. Nalbandyan and Leo, did not have any certain answer to that question. Among the questions raised, one can underline the question of the religious affiliation of the Mkhitarists and their concern to Grabar (Old Armenian) and Ashkharhabar (New Armenian). The Mkhitarists played an important role in the study of Armenology, and made an inestimable contribution to this area.
Keywords: Philology; Linguistics; Language and Literature